Immune Reconstitution Inflammatory Syndrome Secondary to Autoimmune Hemolytic Anemia and Cryptococcal Meningitis - Yin, SiJia; Xu, Yan; Huang, Jinsha; Xiong, Nian; Han, Chao; Ma, Kai; Guo, Xing Fang; Xia, Yun; Wan, Fang; Kou, Liang; Sun, Yadi; Wu, Jiawei; et al. (Frontiers in Neurology, 2019)
A 47-year-old HIV-seronegative woman with Autoimmune Hemolytic Anemia was treated with corticosteroids for 8 months. She developed central nervous system dysfunction and was diagnosed with cryptococcal meningitis after detecting cryptococcus neoformans in the cerebrospinal fluid. The patient’s clinical symptoms worsened and unusual MRI findings of white matter lesions were noticed even after adequate treatment, which are quite unusual compared with typical characteristics of cryptococcal meningitis; this led us to carry out further investigations. Similar cases have been previously reported in published literature. Combined with clinical symptoms and MRI findings, the most likely diagnosis was Cryptococcal Meningitis-Immune Reconstitution Inflammatory Syndrome. Unfortunately, the patient deteriorated and died of respiratory failure. Cryptococcal Meningitis-Immune Reconstitution Inflammatory Syndrome may have MRI changes during the early onset of the disease (bilateral basal ganglia). We propose that close monitor the condition, meticulous MRI follow-up and brain biopsies are indicated in such cases to actively treating them so as to avoid worsening of the patients’ condition.